OPTIMIZATION OF KINETIN CONCENTRATIONS AND MEDIUM COMPOSITIONS FOR CITRUS SHOOT MULTIPLICATION FROM COTILEDONARY NODE - Kristianto Nugroho; Mia Kosmiatin; Tri Joko Santoso; Dewi Sukma; Agus Purwito; Ali Husni; Chaireni Martasari (SEAMEO BIOTROP, 2024)
Plant regeneration post-genetic transformation play an important an role in genome editing activities that should be optimized via several factors such as the composition of the medium and the concentration of plant growth regulators. This study aimed to optimize the kinetin concentrations and medium compositions for shoot multiplication originating from cotyledon node explants of several local citrus cultivars. The cotyledonary nodes from three citrus cultivars (Batu 55, Siam Madu, and Proksi-1 Agrihorti) were incubated in MS medium with Morel and Wetmore vitamins (VMW) supplemented with several kinetin concentrations (0; 0.2; 0.4; 0.6; 0.8; and 1 mg/L). The best kinetin concentrations for number of shoots variable were then combined with MT medium. The results showed that kinetin concentration at 0.8 mg/L gave the best number of shoot in Batu 55 cultivar as well as 1 mg/L concentration in Siam Madu and Proksi-1 Agrihorti cultivars. The combination 1 mg/L kinetin with Murashige and Tucker (MT) medium showed the best number of shoots, percentage of shoot formation, number of leaves, number of nodes, and shoot length in this study. This medium composition could be further used for shoot multiplication in genetic transformation in those three citrus cultivars, including genome editing activities in development of new improved citrus varieties.